2016
DOI: 10.18632/oncotarget.8585
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-related cell death by pan-histone deacetylase inhibition in liver cancer

Abstract: Autophagy is a homeostatic, catabolic degradation process and cell fate essential regulatory mechanism. Protracted autophagy triggers cell death; its aberrant function is responsible for several malignancies. Panobinostat, a potent pan-deacetylase inhibitor, causes endoplasmic reticulum stress-induced cell death. The aim of this study was to investigate the role of autophagy in deacetylase inhibitor-triggered liver cancer cell death.HepG2 (p53wt) and Hep3B (p53 null) liver cancer cell lines were exposed to pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 54 publications
1
30
0
1
Order By: Relevance
“…The number of autophagosome vesicles was quantified based on a previously published method [ 13 , 32 , 33 ]. Statistical analysis was performed, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of autophagosome vesicles was quantified based on a previously published method [ 13 , 32 , 33 ]. Statistical analysis was performed, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy describes the ability of eukaryote cells to degrade cellular molecules, organelles and proteins using autophagosomes as carriers [ 24 ]. Normally the induction of autophagy related cell stress is linked to the promotion of cell survival but [ 25 ], under certain conditions, elevated autophagy levels lead to cell demise representing an alternative way of cell death [ 13 , 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar data in sarcoma cells using the multi-kinase inhibitor pazopanib combined with the novel HDAC inhibitor AR42 also resulted in a clinical trial (NCT02795819). Others have also demonstrated that autophagy is frequently a mechanism by which GI tumor cells can be killed by anti-cancer drugs, using the chemically dissimilar HDAC inhibitor panobinostat [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that its modulation can be a promising target for cancer therapy in liver cancer. [13] The expression of miRNAs repressing autophagy regulators like AMPK could highlight the variations occurring at epigenetic level conferring to cells an altered metabolism that irreversibly modifies the liver cells and tissue. These alterations could be responsible to trigger further pathological cellular features leading to cirrhosis and furthermore liver carcinogenesis.…”
mentioning
confidence: 99%